APT imaging of hepatocellular carcinoma signals an effective therapeutic response in advance of tumor shrinkage - Xiaojing Wang; Keisuke Ishimatsu; Junjie Li; Xiaodong Wen; Weijun Ou; Arnida Anwar; Jaideep Chaudhary; Masaya Takahashi; A Dean Sherry; Ian R Corbin (Hepatic Oncology)
Aim: The aim of this study was to assess the utility of weighted amide proton transfer (APTw) MRI in three different rodent models of hepatocellular carcinoma (HCC).Methods: APTw MRI was evaluated in models of diethylnitrosamine (DEN) induced HCC, N1S1 syngeneic orthotopic xenograft and human HepG2 ectopic xenograft.Results: All models of HCC showed a higher APTw signal over the surrounding normal tissues. In the DEN model, the APTw signal could differentiate HCC lesions from benign nodules. Intra-arterial administration of low-density lipoprotein docosahexaenoic acid (LDL-DHA) nanoparticles to N1S1 xenografts rapidly lowered the tumor APTw signal within 72 h. Direct injections of LDL-DHA nanoparticles into HepG2 xenografts also showed similar therapeutic responses.Conclusion: We have demonstrated the utility of APTw imaging in the diagnostic/therapeutic management of HCC.